MRI Definition of Involved Muscle in Duchenne Muscular Dystrophy - J Gordon Millichap (Pediatric Neurology Briefs)
The degree of muscle involvement of lower leg muscles of 34 patients with DMD >8 years, using muscle MRI, was estimated in a multicenter study at the Institute of Child Health and other centers in London, in the UK, and 1 in Rome, Italy.